Rāgas of the Kathmandu Valley: The Change in Meaning and Purpose - Nepal, Bigyesh (Nepal Journal of Multidisciplinary Research, 2019)
The rāga tradition has been a gem of a musical genre in the Indian subcontinent. Many sources infer that this tradition was also popular in the royal courts of the Mallas. As the Mallas were pious kings, they adroitly designed a musical genre that could gratify both the need of an artist and a worshiper through the application of rāgas. They also established music communities among commoners to sing the rāgas in numerous temples and shrines of the valley. The tradition has been continuing incessantly but the context is not entirely the same. The singers of today sing the songs and the rāgas latent within, but do it out of faith and obligation; as to how a priest practices his rituals, not necessarily how an aesthete sings his song. The rāga culture, voyaging from the kings to the commoners, has gone through a major transformation that has altered the meaning and purpose it availed. As a comparative study on the significance of rāgas in the Malla court and Newar locality has not been done previously, this paper fulfills the gap by sketching the metamorphosis and outlining the function and significance of the same tradition in two distinctly different backdrops.